The lion's whiskers and other Ethiopian tales - Ashabranner, Brent K., 1921-2016; Davis, Russell G; Siegl, Helen (North Haven, Conn. : Linnet Books, 1997)
A collection of folktales from the nine tribes of Ethiopia, along with two stories from Ethiopia's religious traditions
Hyena man -- Lion's whiskers -- King's black curtain -- Snake in the bottle -- Digit the midget -- Lion bones and the Gardula magicians -- Wise judge -- King Firdy the just -- Ant and the tower to God -- Lion's share -- Know your own strength -- Saint Gabre Manfas and his animals -- King Solomon and the Queen of Sheba -- Gift and the giver -- Three suitors -- Talkative turtle
Revised edition of: The lion's whiskers : tales of high Africa / by Russell Davis and Brent K. Ashabranner
Keywords: Tales -- Ethiopia -- Juvenile literature